(untitled) (International Journal of Food and Nutritional Sciences, 2022)
This research paper explores contemporary social issues and examines sociological solutions to address these challenges. It delves into pressing issues such as inequality, mental health, climate change, and digital transformation. By analyzing these problems through a sociological lens, the paper aims to propose actionable solutions based on theoretical and empirical insights. The research highlights the role of sociological theories in understanding social phenomena and suggests strategies for mitigating modern social issues.